Tips for Statistical Tools for Research Methods in Exercise and Sport Sciences - Aliberti, Sara; D'Elia, Francesca; Cherubini, Domenico (Physical Education Theory and Methodology, 2023)
Study purpose. The increasing amount of research in Exercise and Sport Sciences emphasized the use of increasingly heuristic statistical tools appropriate to the aim in terms of qualitative, quantitative, and qualitative-quantitative data. Often, a lack of knowledge of statistical tools and their appropriateness for data analysis, especially between the use of parametric and non-parametric statistical techniques, is encountered by researchers. This requires the indispensable use of statistical experts, who, for the comprehensive understanding of the research design, need the use of human and economic resources that could probably be used differently and more efficiently. The aim of this study was to provide a list of the most used statistical methods in Exercise and Sport Sciences, focusing on the distinction between parametric and non-parametric statistical processing for both quantitative and qualitative research. Materials and methods. The method was the literature review with argumentative elaborations concerning the validity of the use of the statistical tools. Results. A total of 22 statistical tools, both parametric and non-parametric, were found: 5 useful to test relationship, 7 to compare two groups and 10 to compare two or more groups. For each statistical tool, a scientific paper related to Exercise and Sport Sciences was collected. Conclusions. These data allow developing potential guidelines, applying to Exercise and Sport Sciences, for the rigorous model of research projects with a systematic use of statistical processing in the complete hypothesis of the study.